Social interaction and cultural exchange among educational tourist and local community: the case of Famagusta, North Cyprus - Yorganci, Ilkay; Ndukauba, Precious (Emerald Group Publishing Ltd, 2024)
PurposeThe aim of this paper is to investigate the social interaction between international students and the local community in the small university town of Famagusta, North Cyprus. The objectives of the study are, firstly, to investigate the nature of interaction between two communities; secondly, to ascertain the main factors impacting social interaction and, finally, to identify the impact of this interaction on cultural exchange.Design/methodology/approachUsing a qualitative approach, the researchers conducted 39 semi-structured interviews with international students and members of the local community to gain depth and detail.FindingsThe results showed that there was a lack of interaction between the international students and locals due mainly to language barriers.Originality/valueThis study addresses a gap in the literature on educational tourism by focusing on the social interaction between foreign students and the host community in a nontraditional destination. It also provides guidelines for universities, local and national governments on how to build a better quality of life for the community and for international students.
Keywords: Educational tourism; Resident perception; International students; Social interaction; Cultural exchange; North Cyprus